REVOLUTIONIZING CONSERVATIVE BANKING THROUGH FINTECH SERVICES - A STRUCTURAL EQUATION MODELING APPROACH - Dr. Mahesh Kumar.T, Dr. S.Chitra, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Fintechs are generally start-up know-how and financial capability companies, provided that domain-specific products and amenities are delivering by numerous traditional financial organizations such as banks, asset management companies, and insurance enterprises. A Fintech is a financial savvy vessel that can term a developing financial service segment of the 21st Era. The term initially applied to technology interrelated with the back end of recognized customer and trade financial organizations. After globalization, there has been a revolution with an incredible influence on the banking products/ service space. Globalization created great competition, a broader market, a large customer base, access to advanced technology and processes know-how, associated topographical gaps. It opened the doors of communication for various deals. The technology boom in developed and emerging nations has gradually stirred from internet banking to mobile banking and now captivating a new-fangled way towards digital banking. We can see a new uprising progressing with a growth in mobile gadgets, telecom, and data services at inexpensive costs. Hence, this study analyzes conservative banking through fintech services in Chennai city by using statistical tools like factor analysis and Structural Equation Model (SEM).